The Frequency and Major Determinants of Depression in Patients with Rheumatoid Arthritis - Behnaz BEHNAM,; Jamileh MOGHIMI,; Raheb GHORBANI,; Farahnaz GHAHREMANFARD, (Archives of Rheumatology, 2013)
Objectives: This study aims to investigate the relationship between the prevalence of depression and its severity in Iranian patients with rheumatoid arthritis (RA) and to identify useful clinical correlations of the depressive symptoms. Patients and methods: One hundred and forty patients (28 males, 112 females; mean age 46.4±13.5; range 19-80 years) who met the American College of Rheumatology (ACR) criteria for RA in the outpatient rheumatology clinic of the Fatemieh and Amir hospitals in Semnan were included. The patients were divided into two groups including patients with active RA (n=56) and with inactive RA (n=84). One hundred and forty age and gender-matched healthy volunteers who work at the hospital without a history of rheumatological disorder were also included as controls. Depressive symptoms were assessed using the Iranian version of the Beck Depression Inventory II (BDI-II). Results: The overall prevalence of mild-to-moderate depression was 30.4% in the active RA group, 22.6% in the inactive RA group, and 12.1% in the control group. Severe depression was only observed in two of the subjects. One of those was in the active RA group, and the other was in the control group. Multivariate analysis showed that female gender as well as levels of erythrocyte sedimentation rate and C-reactive protein were associated with the development of depression in RA patients. Conclusion: The overall prevalence of mild-to-moderate depression in patients with active RA is notably higher. Thiscan be strongly associated with the gender and serum inflammatory markers.